Assessment on slope mapping using airborne laser scanning and terrestrial laser scanning / Khairul Farhanah Khairon and Khairul Nizam Tahar - Khairon, Khairul Farhanah; Tahar, Khairul Nizam (Faculty of Architecture, Planning & Surveying and UiTM Press, 2014)
This study is about the evaluating the differences of two techniques of Airborne Laser Scanning (ALS) and Terrestrial Laser Scanning (TLS), by carried out an assessment on slope mapping. This study is carried by assessing the Digital Terrain Model (DTM) of a slope in Habu, Cameron Highland Pahang. The further slope assessment is done based on the difference slope class using slope map and slope aspect by ALS technique and TLS technique. These two techniques of data collection provide a three dimensional data point. However, since both techniques is operating in a different platform where the ALS is a kind of data collection from the air platform while TLS is only based on the ground surface, there might be a slight differences in data production even though the use of the same slope is controlled. Hence, at the end of this study, the differences between these two data collection of ALS and TLS could be compared.